2021
DOI: 10.1080/21655979.2021.1996019
|View full text |Cite
|
Sign up to set email alerts
|

Biofuel production from Macroalgae: present scenario and future scope

Abstract: The current fossil fuel reserves are not sufficient to meet the increasing demand and very soon will become exhausted. Pollution, global warming, and inflated oil prices have led the quest for renewable energy sources. Macroalgae (green, brown, and red marine seaweed) is gaining popularity as a viable and promising renewable source for biofuels production. Numerous researches have been conducted to access the potential of macroalgae for generating diverse bioproducts such as biofuels. The existence of componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(14 citation statements)
references
References 101 publications
1
11
0
2
Order By: Relevance
“…In addition, Bao et al (2015) used satellite data and a numerical model (FVCOM) to study the drift trajectory of green algae under tidal and surface winds, and found that wind became the dominant drift force of floating green algae in the northern Jiangsu shoal. This is consistent with satellite tracking of northward U. prolifera movement [ 12 , 14 ] and cruise observations [ 20 ].…”
supporting
confidence: 89%
See 3 more Smart Citations
“…In addition, Bao et al (2015) used satellite data and a numerical model (FVCOM) to study the drift trajectory of green algae under tidal and surface winds, and found that wind became the dominant drift force of floating green algae in the northern Jiangsu shoal. This is consistent with satellite tracking of northward U. prolifera movement [ 12 , 14 ] and cruise observations [ 20 ].…”
supporting
confidence: 89%
“…To date, most research on macroalgal biomass use has focused on renewable energy sources. Current fossil fuel reserves are insufficient for the increasing demand of the expanding human population and will become depleted [ 10 , 12 ]. Production of biofuels (bio-gas, bioethanol, and crude oils) by macroalgae is potentially an environmentally sustainable option [ 1 , 12 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Biomassa laut termasuk alga, saat ini menjadi pertimbangan untuk mengatasi isu pemanasan global dan sebagai alternatif bahan bakar nabati, karena memiliki produktivitas yang tinggi [1] . Makroalga sangat potensial sebagai sumber biofuel karena tidak dapat dikonsumsi, dapat tumbuh eksponensial dalam air garam, kondisi buruk, dan dalam air asin [2] . Kandungan karbohidrat dan lipid pada rumput laut dianggap dapat menjadi sumber energi terbarukan generasi ke-3 [3] .…”
unclassified